2nd INTERNATIONAL SYMPOSIUM of DOHaD and STRESS: METABOLISM, EXERCISE, STRESS and BEHAVIOR - The 2nd International Symposium of DOHaD; Stress (2ndISDS)The 2nd International Symposium of DOHaD (Arquivos do Mudi, 2018)
In the last decades, a group of diseases has gained importance in human health, which are called, non-communicable diseases (NCD), among them its highlighted cardiovascular disease, diabetes and cancer. Recently, World Health Organization has estimated that this group of diseases has been doing more than 41 millions of victims every year, being between the main causes of death worldwide. The explanation that those diseases are exclusively caused by an inadequate lifestyle it’s not sufficient to explain the rapid growth in the prevalence worldwide. A series of epidemiologic and experimental studies has shown evidences that these diseases may be caused by stressor events suffered by the subject during critical phases of his development (pre-conception, lactation, infancy and adolescence), programming his organism to the development of cardiometabolic diseases during adult life, being able to affect next generations. In this sense, the DOHaD (Developmental Origins of Health and Disease) concept, search to clarify what are the susceptible phases to the programming of the organism, as well what are the insults that can initiate this phenom. The 2nd International Symposium of DOHaD and Stress (2ndISDS) approached the DOHaD concept, applied in differente themes, such as: metabolism, exercise, behavior and reproduction. The 2ndISDS promoted the interaction and change of experiences between researchers, professor and students of graduation and post-graduation that act in different areas (Biological Sciences, Biomedicine, Medicine, Biotechnology, Physical education, Nutrition, among others). The first edition of ISDS occurred in 2017 at Buenos Aires, Argentina, being it second edition made in the State University of Maringá, bringing together Brazilian lecturers from UNICAMP, USP, UFRGS, and researchers from Argentina, Mexico and USA worldwide recognized for their works regarding the themes of the symposium. There was participation of 80 congressmen, distributed between researchers, professors, post-graduation and graduation students from different universities. The congressmen had the opportunity to present works approaching the themes of the symposium and discuss them with internationally renowned researchers. Thus, the 2ndISDS 2018 had come to Brazil with the mission of spread the DOHaD concept and integrate the academic society around discussions that bring advances to the researches in favor of health and life, in all his phases of development. Paulo Cézar de Freitas Mathias Lucas Paulo Jacinto Saavedra Silvano Piovan